Dinamika Pembelajaran Bahasa Indonesia di Kelas Rendah Sekolah Dasar di Era Globalisasi - Siti Khodijah Marpaung; Mu’thiya Hasanah; Khairunisa Azura B.r Panjaitan; Revalina Maisyaroh; Nadia Bismi Hafifah (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Indonesian language learning in lower elementary school grades faces various changes in the era of globalization, particularly due to technological developments, changes in student characteristics, and demands for literacy strengthening. This study aims to describe the dynamics of Indonesian language learning in lower elementary school grades in the era of globalization, including planning, implementation, technology utilization, obstacles, and teacher strategies. This study uses a descriptive qualitative approach with purposive selection of informants consisting of lower elementary school teachers as primary informants and principals and students as supporting informants. Data were collected through observation, in-depth interviews, and documentation, then analyzed using an interactive model through data condensation, data presentation, and drawing conclusions. The results show that Indonesian language learning has integrated active methods and digital media to create more interactive and student-centered learning. However, its implementation still faces obstacles such as limited technological facilities, teachers' digital competencies, differences in students' literacy abilities, and lack of parental guidance. Strategies implemented by teachers include literacy strengthening, the use of innovative media, individual guidance, and collaboration with parents. This study concludes that innovation in Indonesian language learning in the era of globalization needs to be supported by improved teacher competency, adequate facilities, and synergy between schools and families.